Development Strategy of Potential Micro-Location Castle Kerestinec and Sustainable Ideas for Its Revival - Jarc, Nika Iza; Rovčanin, Anja; Olie, Senna (Program održivog razvoja Svete Nedelje, Jastrebarskog i Samobora, 2024)
This paper focuses on a potential Croatian local-level destination Castle Kerestinec in the town of Sveta Nedelja which is a part of Zagreb County and is located in the immediate proximity of the city Samobor and the capital, Zagreb. It defines the basic concepts of large and local level destinations, sustainable tourism and within its heritage/cultural tourism, educates about the history of Castle Kerestinec and analyses its current situation and possibilities for tourism development. The analytical part of the paper covers the current tourism situation in the town of Sveta Nedelja with basic statistics of accommodation capacities and the number of arrivals. There are main tourist attractions presented as well as a possible tourist segmentation and SWOT analysis of Castle Kerestinec, the prospective part presents ideas which were highlighted by the tourist board of Sveta Nedelja and some of our ideas and suggestions for the future development of Castle Kerestinec. A possible strategy for development is presented through specific priority areas, measures and indicators. In conclusion, the paper emphasizes that Castle Kerestinec has the potential to become a cultural center through adaptive reuse, that will bring together locals and visitors from different countries.